Motivasi Berprestasi Atlet Muda dalam Menghadapi Pekan Olahraga Nasional Tahun 2012 Ditinjau dari Kepercayaan Diri - Syarifah Farradinna (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2012)
The aim of this study is to analyze the correlation between self confidence and achievement motivation, and also to find out the impact of self confidence on athletes' achievement motivation while facing the 18th PON. Subjects in this research are 99 young athletes from Riau, male and female, that are going to face the 18th PON in 2012. This study is modify Moore's Self Confident Scale and Falah Yunus' Achivement Motivation Scale. This study use Pearson's Product Moment Correlation to examine whether there is a correlation between self confidence and athletes' achievement motivation, while facing the 18th PON in 2012. This study also use the Regression Analysis to find out the impact of self confidence on athletes' achievement motivation while facing the 18th PON. Data analysis shows r= 0.371 and p = 0.000 (p < 0.001) which means that there is a very significant positive correlation between self confidence and achievement motivation. From the result of the study, we can conclude that self confidence has impact on achievement motivation.Keywords: self confidence, achievement motivation